The nano-bio interactions of rare-earth doped BaF2 nanophosphors shape the developmental processes of zebrafish. (28th October 2020) - Chouryal, Yogendra Nath; Nema, Shubham; Sharma, Rahul Kumar; Kewat, Heera Lal; Pandey, Archna; Ghosh, Pushpal; Bhargava, Yogesh
Abstract : Nanoparticles with biomedical applications should be evaluated for their biocompatibility. Abstract : Nanoparticles with biomedical applications should be evaluated for their biocompatibility. Rare-earth doped nanoparticles with unique spectral properties are superior in vivo optical probes in comparison with quantum dots and organic dyes, however, studies describing their nano-bio interactions are still limited. Here, we have evaluated the nano-bio interactions of green-synthesized, phase-pure BaF2 nanoparticles doped with rare-earth (RE 3+ = Ce 3+ /Tb 3+ ) ions using larval zebrafish. We found that zebrafish can tolerate a wide concentration range of these nanoparticles, as the maximal lethality was observed at very high concentrations (more than 200 mg L −1 ) upon five days of continuous exposure. At a concentration of 10 mg L −1, at which Zn 2+, Ti 4+ and Ag + nanoparticles are reported to be lethal to developing zebrafish, continuous exposure to our nanoparticles for four days produced no developmental anomalies, craniofacial defects, cardiac toxicity or behavioural abnormalities in the developing zebrafish larvae. We have also found that the doping of rare-earth ions has no major effect on these biomarkers. Interestingly, the function of acetylcholinesterase (AChE) and the cellular metabolic activity of whole zebrafish larvae remained unchanged, even during continuous exposure to these nanoparticles at 150 mg L −1 for four days; however, severe developmental toxicities were evident at this high concentration. Based on these results, we can conclude that the biocompatibility of rare-earth doped nanoparticles is concentration dependent. Not all biomarkers are sensitive to these nanoparticles. The high concentration-dependent toxicity occurs through a mechanism distinct from changes in the metabolic or AChE activity. The significance of these findings lies in using these nanoparticles for bioimaging applications and biomarker studies, especially for prolonged exposure times.